Analysis of effects of 5-azacytidine on promoting flowering in non-heading chinese cabbage - LI Mei-lan; ZENG Guang-wen; ZHU Zhu-jun (浙江大学学报. 农业与生命科学版)
The treatment of the seeds with 5-azacytidine promoted flowering at low concentration but inhibited flowering at high concentration in non-heading chinese cabbage. The optimum concentration was 250 μmol/L. In addition the effects of 5-azacytidine were additive with low temperature. 5-azacytidine decreased DNA methylation level and gibberellin content. These results indicated that 5-azacytidine could substitute for the effects of low temperature in flower promotion.